PARTISIPASI KELOMPOK TANI DALAM PENINGKATAN PRODUKTIVITAS TANAMAN PADI DI KAWASAN PERTANIAN KECAMATAN KURANJI - Marna Adisa Pitri; Ratna Wilis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The agricultural sector in Kuranji District is a key economic driver, particularly in Padang City. The objectives of this study are (1) to describe and discuss the level of participation of farmer groups in the agricultural areas of Kuranji District, and (2) to describe and discuss the level of rice productivity in the agricultural areas of Kuranji District. This study used a quantitative descriptive method. The population and sample were members of farmer groups in Kuranji District. The sampling technique used proportional random sampling, resulting in 95 farmer group members. Data collection techniques included questionnaires, interviews, and documentation. The data analysis used descriptive analysis using a Likert scale to measure participation levels. The results showed that the level of participation of farmer groups in Kuranji District was classified as high, with a total score of 3,427, or 80.16%. The average level of rice productivity in Kuranji District was moderate, at 4.8-6.3 tons/ha. The highest productivity was 8 tons/ha, and the lowest productivity was 3 tons/ha.